2011
DOI: 10.4049/jimmunol.1000284
|View full text |Cite
|
Sign up to set email alerts
|

Absent Bactericidal Activity of Mouse Serum against Invasive African Nontyphoidal Salmonella Results from Impaired Complement Function but Not a Lack of Antibody

Abstract: Nontyphoidal strains of Salmonella are a major cause of fatal bacteremia in Africa. Developing a vaccine requires an improved understanding of the relevant mechanisms of protective immunity, and the mouse model of Salmonella infection is useful for studying immunity to Salmonella in vivo. It is important to appreciate the similarities and differences between immunity to Salmonella in mice and men. Ab is important for protection against nontyphoidal Salmonella in both species, and we have previously found an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 36 publications
(47 reference statements)
4
31
0
Order By: Relevance
“…Even when these obstacles are overcome, there remains the added complication of obtaining enough complement for use in multiple studies and across laboratories. We did not attempt to use mouse complement because Siggins et al (38) showed that mouse complement is unable to kill S. Typhimurium in the presence of human anti-Salmonella antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Even when these obstacles are overcome, there remains the added complication of obtaining enough complement for use in multiple studies and across laboratories. We did not attempt to use mouse complement because Siggins et al (38) showed that mouse complement is unable to kill S. Typhimurium in the presence of human anti-Salmonella antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive NTS is endemic in sub-Saharan Africa where it is a leading cause of fatal bacteremia among African children and HIV-infected adults. Increasing levels of antibiotic resistance among African strains of NTS indicate that a vaccine is urgently needed (Siggins et al, 2011). In Malawi, MacLennan et al (2008) recently found that NTS bacteriemia particularly affects African children between 4 months and 2 years of age, the period in which immunoglobulin levels to NTS are low or absent.…”
Section: Salmonellosis -An Emerging Problemmentioning
confidence: 99%
“…Although the murine model of Salmonella infection has been widely studied, its utility as a preclinical model of human Salmonellosis remains unclear (28,52). We therefore examined antigen targeting using a well-characterized set of convalescent pediatric sera from 12 children admitted to hospital with Salmonella bacteremia or meningitis in Blantyre, Malawi, where NTS bacteremia is common in young children (16), and age-and sex-matched healthy controls.…”
Section: Antigenic Targeting During Salmonellosis In Malawian Childrenmentioning
confidence: 99%